Weapon of choice: fighting gun violence while respecting gun rights - Ayres, Ian (Harvard University Press, 2020)
Preface: Fred's story -- Introduction -- Part I. Empowering self-restriction: Donna's Law -- Analogies, choices, and constraints -- Laboratories of democracy -- Part II. Harnessing others' association preferences: Emails and the associational marketplace -- Libertarian contracting and its limits -- Privatizing gun-free zones -- Part III. Harnessing others' information: Symptom-based gun removal orders -- Unlawful possession petitions -- Incentivizing bottom-up gun control.